Abdominal tuberculosis in urgent surgery (Bangladesh Journal of Medical Science, 2019)
Objective: This article presents retrospective analysis conducted on the basis of the General Surgery Clinic of the Irkutsk State Medical University (ISMU).Materials and methods: 165 cases of abdominal tuberculosis (AT) were detected and analyzed. The sample was made from the total number of patients who were treated in the surgical department for urgent reasons from 2009 to 2018.Results and Discussion: Proportion of hospitalized AT cases from the total number increases every year and slightly decreases only after 2013. The largest number of hospitalizations in 2013 was 29 cases or 2.1%. General characteristics are as follows: 95% of patients were 30–35 years old, 93% used drugs, 80% were HIV positive, and 88.3% suffered abdominal pain. Tuberculosis of the gastrointestinal tract with ulcer perforation was more common (53.7%). 140 (84.5%) patients had history of operation. Overall mortality was 57.6%.Conclusion: The main cause of mortality was generalized tuberculosis. The contribution of these cases to the overall mortality over the period taken was not possible to estimate.Bangladesh Journal of Medical Science Vol.18(4) 2019 p.796-800